Pemetaan Kualitas Permukiman di Kecamatan Kartasura Kabupaten Sukoharjo Tahun 2017 - Setiawan Indra Yulianto; Moh Gamal Rindarjono; Seno Budhi Ajar (Universitas Sebelas Maret (UNS), 2022)
The objectives of this research are (1) to determine the dynamics of settlement density in Kartasura District in 2007 - 2017; (2) knowing the dynamics of settlement patterns in Kartasura District in 2007 - 2017; and (3) determine the quality of settlements in Kartasura District in 2017. The research method used a qualitative method, using a spatial (spatial) approach. Data analysis using inductive analysis techniques. The results of the study (1) the level of settlement density in 2007 - 2017 continued to increase, (2) the quality of settlement patterns in 2007 - 2017 continued to decline, and (3) the quality of settlements in Kartasura District in 2017 was dominated by moderate quality but not a few are of poor quality. Keywords : Quality of Settlements, Dynamics, Settlements